Adenoviral-vectored neoantigen vaccine augments hyperexpanded CD8+ T cell control of tumor challenge in mice - David Li; Gabriel Dagotto; Alessandro Colarusso; Robert C Patio; Tochi Anioke; Victoria Giffin; Ruoran Guan; Trisha Anand; Esther Mbiwan; Malika Aid; Dan Barouch (Journal for ImmunoTherapy of Cancer)
Background Neoantigens are promising immunogens for cancer vaccines and are often delivered as adjuvanted peptide vaccines. Adenoviral (Ad) vectors have been shown to induce strong CD8+ T cell responses as vaccines against SARS-CoV-2, Ebola, and Zika, but their utility as neoantigen delivery vectors remains largely unexplored. In this study, we examine how an Ad-vectored neoantigen vaccine would impact tumor immunity compared with a peptide neoantigen vaccine.Methods We generated Ad serotype 26 (Ad26) vaccine candidates encoding B16-F10-ovalbumin (OVA) and MC38-specific neoantigens. Ad26 vaccines were compared with adjuvanted peptide delivery as prophylactic vaccines in B16-F10-OVA and MC38 challenge models. Immune responses induced by the best Ad26 vaccine (Ad26.VP22.7Epi) were compared with peptide vaccination systemically and within the tumor. Following vaccination with Ad26.VP22.7Epi, peptide, or sham, tumor-infiltrating CD45+ cells were analyzed using single-cell RNA sequencing (scRNA-seq) and T cell receptor sequencing (TCR-seq) to identify vaccine-induced differences in the tumor microenvironment.Results Single-shot Ad26 vaccines induced greater neoantigen-specific interferon-γ CD8+ T cell immune responses than two-shot adjuvanted peptide vaccines in mice, and Ad26.VP22.7Epi also provided superior protective efficacy compared with the peptide vaccine following tumor challenge. Ad26.VP22.7Epi induced a robust immunodominant CD8+ T cell response against the Adpgk neoantigen, while the peptide vaccine-induced lower responses against both Adpgk and Reps1 neoantigens. scRNA-seq analysis of CD45+ tumor-infiltrating cells demonstrated that both Ad26.VP22.7Epi and peptide vaccine-induced similar numbers of infiltrating CD8+ T cells. However, Ad26.VP22.7Epi induced CD8+ T cells showed more upregulation of T cell maturation, activation, and Th1 pathways compared with peptide vaccine induced CD8+ T cells, suggesting improved functional T cell quality. TCR-seq of these tumor-infiltrating lymphocytes also demonstrated that Ad26.VP22.7Epi generated larger T cell hyperexpanded clones compared with the peptide vaccine.Conclusions These results suggest that the Ad26.VP22.7Epi vaccine led to improved tumor control compared with the peptide vaccine due to increased T cell hyperexpansion and functional activation. Our data suggest that future cancer vaccine development strategies should focus on inducing functional hyperexpanded CD8+ T cell responses and not only maximizing tumor infiltrating CD8+ T cell numbers.